Extended reverse sural artery pedicle flap: a versatile and reproducible option for coverage of ankle and foot defects - Patil, Bhushan R.; Wahegaonkar, Chandrashekhar; Agarkhedkar, Nikhil; Dogra, Bharat Bhushan (International Journal of Research in Medical Sciences, 2019)
Background: Coverage of soft tissue defects around distal third of the leg, particularly ankle and foot is a common situation faced by a plastic and reconstructive surgeon. Options available for such defects are limited due to scarcity of additional soft tissue that can be used without exposing tendons or bone. Associated conditions such as major vascular compromise, comorbidities and lack of facilities or expertise make free tissue transfer less preferred. Distally based sural artery flap has been a frequently used flap in such conditions, easy to perform and has reproducible results. We extended the reach of the flap and reproduced the results. Methods: We performed extended reverse sural artery pedicled flaps in 19 patients who presented to us between 2015 to 2017 with soft tissue defects around ankle and foot. Patients included 15 post RTA, 2 diabetic foot, 1 post resection defect and 1 post burn contracture release defect. Size of the defect ranged between 8x6cm to 14x10cm. Average follow up period was ranging from 8 months to 2.5 years. Results: All the flaps healed well without any obvious complications except one patient in whom marginal necrosis (2 cm margin of distal most flap) was observed and was secondarily treated with skin grafting. Conclusions: We observed that extended reverse sural pedicle flap is a rapid, reliable option for coverage of soft tissue defects around ankle and heel, sparing major vessel compromise and lengthy surgical procedure during free tissue transfer. This flap should be the first option for the patients with trauma and defects over weight bearing foot in whom peroneal axis vessels are preserved.